Never rarely sometimes always [videorecording (DVD)] - Hittman, Eliza; Flanigan, Sidney; Ryder, Talia; Eggold, Ryan, 1984- (Universal Studios Canada, 2020)
Faced with an unintended pregnancy and a lack of local support, Autumn and her cousin Skylar embark across state lines to New York City on a fraught journey of friendship, bravery, and compassion.